2022
DOI: 10.2991/978-94-6463-052-7_13
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Chinese Stock Investor Sentiment Index

Abstract: Based on some data of the CSI 300 index, this paper uses the principal component analysis (PCA) to build the investor sentiment index, and then discusses the feasibility of constructing the investor sentiment index. It aims to build an investor sentiment index that matches the Chinese market, understand the psychological characteristics of investors, predict their expectations, and formulate effective regulatory policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A common example of this is that retail investors often get trapped in stock trading. General market empirical factors research analytical models and predictive findings of comparative analysis have shown that investor sentiment once overly excited high after often does produce a rapid response to improve the market's overall current stock price expectations and returns [12]. The endowment effect often causes you to make irrational judgments about the value of what you have.…”
Section: Endowment Effectmentioning
confidence: 99%
“…A common example of this is that retail investors often get trapped in stock trading. General market empirical factors research analytical models and predictive findings of comparative analysis have shown that investor sentiment once overly excited high after often does produce a rapid response to improve the market's overall current stock price expectations and returns [12]. The endowment effect often causes you to make irrational judgments about the value of what you have.…”
Section: Endowment Effectmentioning
confidence: 99%